Pelatihan dan Penyuluhan mengenai Bahaya Kanker Serviks pada Kelompok Ibu-ibu Pengajian di Pangkalan Jati, Cinere, Depok - Tiwuk Susantiningsih; Feda Anisah Makkiyah; Yuni Setyaningsih (Universitas Mathla'ul Anwar Banten, 2020)
TRAINING AND EDUCATION ABOUT THE DANGER OF CANCER SERVICS IN WOMEN GROUP OF PANGKALAN JATI, CINERE, DEPOK. Cervical cancer was a chronic disease due to a tumor in the cervix that was uncontrolled tissue growth and damage to the surrounding normal tissue. Citizen still does not understand the signs of disease and its dangers. Early screening of cervical cancer was done with the aim to reduce the incidence of cervical cancer. Based on an analysis of the situation and the results of a preliminary survey, the problems faced by partners are the lack of knowledge and skills of women about cervical cancer, as well as its prevention in RT 007/RW 007, Pangkalan Jati Village. This program counseling activities about the dangers of cervical cancer can be well received by the counseling participants seen with enthusiasm and questions raised. Participants gained additional knowledge about the dangers of cervical cancer, it can be seen by the presence of an increase in the value of post-test after counseling about the dangers of cervical cancer by 2%, from 84% to 86%.